A Critical Analysis of Inflation-Hedging Capacity of Packaging Stocks in Nigeria - NWUDE , E Chuke (Asian Journal of Empirical Research, 2013)
This paper investigates the extent to which stocks of packaging firms listed in Nigerian Stock Exchange (NSE) are a hedge against the actual inflation in Nigeria over the period 2000–2011. Actual inflation is computed as the estimates of the consumer price index.The study used real rate of return on equity and regression analysis to find the stocks that provide positive real return and offer inflation-hedging potentials respectively. The findings revealed that in terms of real return based on shareholders’ funds and total return to equity, all the firms were not susceptible to adverse effect of inflation but when based on dividend yield all the firms offered no significant hedge against inflation.